MENGENALI GIFTED PADA ANAK MELALUI PERKEMBANGAN BAHASA - Syasli, David (Universitas Tanjungpura, 2020)
One language development of children who appear to be less than perfect is gifted or giftedness. This imperfect development received the attention of experts in the fields of language, health, and education, as well as other experts. At present the problem of gifted children is diagnosed with various behavioral disorders, mental disorders, and developmental disorders, so that for the needs of care, guidance, and education for him gifted children should be detected early so that guidance can be given according to their needs. Khalid, a 6-year-old child has gifted characteristics. Khalid's curiosity was so high that he did not take into account the risks of getting answers from his curiosity. When you want something Khalid wants to impose the will, so that the goal is achieved. Khalid is indicated to experience behavioral disorders, mental disorders and is very fond of toy collections. Khalid's parents must be observant and understand the development of their children, because despite having behavioral, mental disorders and fans of toy collections, Khalid actually has an advantage that is very beneficial for his future such as a very strong desire to do and realize things and have curiosity very high against any phenomenon that interests him. Report on the Development of Students from the school where Khalid learned to show information that Khalid stood out one of them in an attitude of curiosity.Keywords: gifted, development, behavior, mental.